The EPPO/OLAF compendium of national procedures: Lithuania - Hauck, Pierre; Schneider, Jan-Martin; Karakocaoğlu, Nur Sena; Laird, Alastair Alexander; Justus Liebig University Giessen (My University, 2026)
This Lithuanian EPPO/OLAF volume covers the procedures of the European Public Prosecutor's Office (EPPO) in Lithuania, including EU fraud typologies and relevant case law. The volume also contains information and provisions for defence lawyers working against the EPPO in cases of customs, financial, tax, or subsidy fraud. The second part is a guide to OLAF investigations in Lithuania, focusing on information controls and the relationship between national partners and external investigations. An anonymous person has acted as the publication’s national expert.
Keywords: ddc:340; ddc:320